Karrikins enhance light responses during germination and seedling development in Arabidopsis thaliana - Nelson, D.; Flematti, G.; Riseborough, J.; Ghisalberti, E.; Dixon, Kingsley; Smitha, S. (National Academy of Sciences, 2010)
Karrikins are a class of seed germination stimulants identified in smoke from wildfires. Microarray analysis of imbibed Arabidopsis thaliana seeds was performed to identify transcriptional responses to KAR1 before germination. A small set of genes that are regulated by KAR1, even when germination is prevented by the absence of gibberellin biosynthesis or light, were identified. Light-induced genes, putative HY5-binding targets, and ABRE-like promotermotifs were overrepresented among KAR1-up-regulated genes. KAR1 transiently induced the light signal transduction transcription factor genes HY5 and HYH. Germination of afterripened Arabidopsis seed was triggered at lowerfluences of red lightwhen treated withKAR 1. Light-dependent cotyledon expansion and inhibition of hypocotyl elongation were enhanced in the presence of germination-active karrikins.HY5is important for the Arabidopsis hypocotyl elongation, but not seed germination, response to karrikins. These results reveal a role for karrikins in priming light responses in the emerging seedling, and suggest that the influence of karrikins on postfire ecology may not be limited to germination recruitment.